Psychometric validation of the information technology acceptance scale for Chinese high school teacher - Dou, Gang; Feng, Yilin (Frontiers in Education, 2025)
This study aimed to examine the psychometric properties of the Information Technology Acceptance Scale for High School Teachers, developed in Chinese and grounded in the Technology Acceptance Model (TAM). The scale measured four key constructs: perceived usefulness, perceived ease of use, attitude toward technology use, and intention to use. A total of 682 Chinese high school teachers participated by completing a paper-based questionnaire. Confirmatory factor analysis supported a refined 16-item version with a stable four-factor structure and satisfactory model fit. Internal consistency was acceptable to strong across all factors (Cronbach’s α > 0.799, McDonald’s ω > 0.801, construct reliability H > 0.801). Evidence for convergent and discriminant validity was obtained through analyses of average variance extracted, Heterotrait-Monotrait Ratio, and inter-construct correlations. Measurement invariance across gender was established at configural, metric, scalar, and strict levels, and latent mean differences were minimal. Structural equation modeling supported all hypothesized relationships within the TAM framework. Attitude toward use emerged as the strongest predictor of intention to use and also mediated the effects of perceived usefulness and perceived ease of use. The model explained 57.5% of the variance in intention to use. These results provide preliminary but robust psychometric support for the scale and suggest its utility in assessing Chinese high school teachers’ acceptance of educational technology.